Wind Turbine Mounted on A Motorcycle for Portable Charger - G. Subhashini; Raed Abdulla; Thinaga Raj R Mohan (Institute of Advanced Engineering and Science, 2018)
This paper aims to develop a wind energy harvesting system to charger an electronic device of 5V during traveling period from a place to another. Upon the situation faced by the two wheeler depending on the conventional power socket, this system was constructed to overcome the dependencies of power since the natural energy can be harvested to produce an electrical energy. The power storage unit system was done by integrating supercapacitor to storage the electrical energy hence an arduino microcontroller was been integrated with supercapacitor which able to display the percentage and voltage stored in the supercapacitor. The maximum speed of the geared DC generator is 1297 rpm and based on the testing carried out, it was observed that the maximum voltage produce at 1297 rpm able to produce 17V which sufficient to power up the entire system as it required 5.3V for operating. Besides, the system was converted into acrylic board since the system are to be implemented on two wheeler hence the acrylic board was design based on the conform ability of the user. In a nut shell, the functionality of the entire system was successfully achieved based on the objectives and overcoming the drawback from past research work.